La regionalización universitaria en Costa Rica, el caso de la Universidad de Costa Rica en Golfito, 1984-2017 - Fonseca Zúñiga, Edgardo (2019)
This research exposes the development and consolidation of the presence of the University of Costa Rica (UCR) in the Brunca Region in Costa Rica. This began with the donation to the UCR of land and buildings in Golfito, Puntarenas, used until then by the Banana Company of Costa Rica (CBCR) after the abandonment of the banana activity in 1984. These facilities are managed by different entities such as the UCR- Kansas University agreement, the Foundation for Interuniversity Cooperation in the South Pacific (FUCIP) and the UCR Foundation for Research (FUNDEVI). In 2004, the Rectory of the UCR took over the administration of these buildings and in 2006 began teaching tasks, with which it became a university branch.